Translating international guidelines for use in routine maternal and neonatal healthcare quality measurement - Chang, Karen T.; Hossain, Puspita; Sarker, Malabika; Montagu, Dominic; Chakraborty, Nirali M.; Sprockett, Andrea (Taylor & Francis, 2022)
This article was published in Global Health Action [ © 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/)] and the definite version is available at: https://doi.org/10.1080/16549716.2020.1783956 The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/16549716.2020.1783956